Implicit measures of anthropomorphism: affective priming and recognition of apparent animal emotions - Dacey, Mike; Coane, Jennifer H. (Frontiers in Psychology, 2023)
It has long been recognized that humans tend to anthropomorphize. That is, we naturally and effortlessly interpret the behaviors of nonhuman agents in the same way we interpret human behaviors. This tendency has only recently become a subject of empirical research. Most of this work uses explicit measures. Participants are asked whether they attribute some human-like trait to a nonhuman agent on some scale. These measures, however, have two limitations.First, they do not capture automatic components of anthropomorphism. Second, they generally only track one anthropomorphic result: the attribution (or non-attribution) of a particular trait.However, anthropomorphism can affect how we interpret animal behavior in other ways as well. For example, the grin of a nonhuman primate often looks to us like a smile, but it actually signals a state more like fear or anxiety. In the present work, we tested for implicit components of anthropomorphism based on an affective priming paradigm. Previous work suggests that priming with human faces displaying emotional expressions facilitated categorization of words into congruent emotion categories. In Experiments 1-3, we primed participants with images of nonhuman animals that appear to express happy or sad emotions, and asked participants to categorize words as positive or negative. Experiment 4 used human faces as control. Overall, we found consistent priming congruency effects in accuracy but not response time. These appeared to be more robust in older adults. They also appear to emerge with more processing time, and the pattern was the same with human as with primate faces. This demonstrates a role for automatic processes of emotion recognition in anthropomorphism. It also provides a potential measure for further exploration of implicit anthropomorphism.